Correction: Nano-bismuth sulfide based dispersive micro-solid phase extraction combined with energy dispersive X-ray fluorescence spectrometry for determination of mercury ions in waters. Issue 9 (11th August 2021) - Pytlakowska, Katarzyna; Malicka, Ewa; Talik, Ewa; Gągor, Anna
Abstract : Correction for 'Nano-bismuth sulfide based dispersive micro-solid phase extraction combined with energy dispersive X-ray fluorescence spectrometry for determination of mercury ions in waters' by Katarzyna Pytlakowska et al., J. Anal. At. Spectrom., 2021, 36, 786–795, DOI: ; 10.1039/D0JA00477D .